Penguatan Pendidikan Karakter (PPK)Keagamaan Islam Pada Kurikulum 2013 DI KOTA BLITAR - Hanna Aulia; Anshar Ruddin (Universitas Nahdlatul Ulama Blitar, 2021)
In the world of education has been hot and much talked about character building. It is shown by the nation’s character in this globalization era has declined very sharply, and it makes why character education is needed. In addition, technological advances make a person's character change. Based on this situation, this research examines the Scientific Approach (scientific approach) in strengthening character education through social media is reviewed based on a scientific paradigm positivistic initiated by Auguste Comte. The results of this study explain that the scientific approach (scientific approach) in curriculum learning 2013 through the steps of observing, asking, reasoning, associating, and communicate is relevant to the positivistic paradigm. Positivism theory stems from the emergence of the three-stage law (Law of Three Stages) of Auguste Comte. Through this law, he states that the history of the development of thought humans, has developed according to three stages, namely the theological or fictitious stage, the metaphysical or abstract stage, and the positive or scientific or real stage. So in a positivistic perspective that if the scientific approach (scientific appoach) applied to teaching character education in the curriculum 2013 through social media is very appropriate to be applied to the process learning.